Assessing environment and development outcomes in conservation landscapes - Sayer, Jeffrey A.; Campbell, Bruce M.; Petheram, L.; Aldrich, M.; Ruíz Pérez, M.; Endamana, D.; Dongmo, Z.L N.; Defo, L.; Mariki, S.; Doggart, N.; Burgess, Neil D. (2007)
An approach to assessing the environmental outcomes and changes in peoples’ livelihoods resulting from landscape-scale conservation interventions was developed for three locations in Africa. Simple sets of performance indicators were developed through participatory processes that included a variety of stakeholders. The selection of indicators was designed to reflect wider landscape processes, conservation objectives and as local peoples’ preferred scenarios. This framework, combined with the use of social learning techniques, helped stakeholders develop greater understandings of landscape system dynamics and the linkages between livelihood and conservation objectives. Large scale conservation and development interventions should use these approaches to explore linkages and improve shared understanding of tradeoffs and synergies between livelihood and conservation initiatives. Such approaches provide the basis for negotiating and measuring the outcomes of conservation initiatives and for adapting these to changing perspectives and circumstances.